Determining Optimal Alternative Strategies for Solar Panel Machine Productions at PT Len Industry (PERSERO) - Fachri Aliyuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This study aimed to identify the root causes of low annual production capacity and propose optimal alternative strategies to enhance efficiency and output. Methodology/approach: This study integrates Porter’s analysis, stakeholder analysis, and AHP across phases from planning to full-scale operation, aiming at modernization, compliance, competitiveness, and customer satisfaction. Results/findings: The study finds that low production capacity is caused by outdated equipment, weak stakeholder coordination, lack of performance monitoring, and limited adoption of digital technology. Porter’s analysis and AHP conclude that technological modernization is the most effective strategy, with new equipment projected to increase production capacity by 35–45% and improve operational efficiency. Conclusions: Improving production capacity requires a multidimensional approach, including strategic planning, modern technology adoption, and stakeholder engagement. A phased implementation model proves effective in addressing systemic issues while maintaining operations, enhancing competitiveness, and boosting customer satisfaction. Limitations: The study is limited to a specific industry context, so the results may not be widely generalizable. The long-term impact of the strategy remains unclear, and the AHP method involves expert judgment, which introduces subjectivity. Contribution: This study offers a structured framework combining Porter’s analysis, stakeholder analysis, and AHP, showing that phased implementation and technology investment can greatly enhance production performance.